A review of small heat pipes for electronics. (5th March 2016) - Chen, Xianping; Ye, Huaiyu; Fan, Xuejun; Ren, Tianling; Zhang, Guoqi
Highlights: Small heat pipes are the preferred cooling solutions for electronics. The wicks from micro to nano sizes are under development for the ability to enhance the efficiency. Because silicon is widely used in electronics, it is a favoured material for small heat pipes. Polymer-based small heat pies are attractive for their easy fabrication and low cost. Abstract: Heat pipes (HPs) have received considerable attention in recent decades, especially in the field of cooling electronics, which requires the removal of added heat from an area of limited volume to the environment. Small HPs are widely used in electronic applications, which are normally limited by the compact structure and dimensions of the electronic device. Among small HPs, mini/micro HPs and two-phase loops (TPLs) with mini/micro wicks, including loop HPs (LHPs) and capillary pumped loops (CPLs), are preferred for their high efficiency, small dimensions, and compatible process with semiconductor devices. Particularly, TPLs possess all of the main advantages of traditional HPs with the addition of special properties that enable the transfer of heat for distances up to several metres at any orientation in the gravity field. Further, small vapour chambers (VCs), also referred to as flat HPs, are excellent candidates for electronic heat spreaders due to their light weight, geometric flexibility, and extremely high thermal conductivities. Because silicon is widely used in electronics, it is a preferred material for mini/micro HPs along with TPLs. Moreover, polymer-based small HPs are highly attractive for further development as they are inexpensive and easy to fabricate. Because the smaller wicks supply a greater capillary force, nano wicks, such as carbon nanotubes (CNTs), may represent the future of HPs due to their potentially outstanding characteristics. In this work, a review of small HPs, including their design, analysis, and fabrication, is presented.